2007
DOI: 10.1016/j.jtbi.2007.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Second cancers after fractionated radiotherapy: Stochastic population dynamics effects

Abstract: When ionizing radiation is used in cancer therapy it can induce second cancers in nearby organs. Mainly due to longer patient survival times, these second cancers have become of increasing concern. Estimating the risk of solid second cancers involves modeling: because of long latency times, available data is usually for older, obsolescent treatment regimens. Moreover, modeling second cancers gives unique insights into human carcinogenesis, since the therapy involves administering well characterized doses of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 45 publications
1
27
1
Order By: Relevance
“…Previous studies had revealed the most common SPCs were neoplasms of upper aerodigestive organs, lung and thyroid gland in the EC patients (Matsubara et al, 2003;Das et al, 2006). This phenomenon could be interpreted as radiotherapy for esophageal cancers enhanced the risk of developing a second malignancy in nearby organs (Sachs et al, 2007). These results were partially inconsistent with our clinical data because HCC was also shown as one of the most common SPCs in the EC patients in our study.…”
Section: Discussioncontrasting
confidence: 94%
“…Previous studies had revealed the most common SPCs were neoplasms of upper aerodigestive organs, lung and thyroid gland in the EC patients (Matsubara et al, 2003;Das et al, 2006). This phenomenon could be interpreted as radiotherapy for esophageal cancers enhanced the risk of developing a second malignancy in nearby organs (Sachs et al, 2007). These results were partially inconsistent with our clinical data because HCC was also shown as one of the most common SPCs in the EC patients in our study.…”
Section: Discussioncontrasting
confidence: 94%
“…Many mathematical models have been proposed to describe the dose-response relationship for radiationinduced cancer [2][3][4]. Some models are applicable in low-dose regions and have to be extrapolated to higher doses relevant for radiotherapy [5].…”
Section: Description Of Modelmentioning
confidence: 99%
“…This study has not considered the effect of cell repopulation during treatment as, in most instances, the radiation cancer and sarcoma induction will occur in very slowly dividing cell systems such as basal cells of skin, connective tissues, meninges, glial tissues, thyroid and prostate, which emerge from very stable tissues and are associated with low repopulation rates. For tissues that repopulate during radiotherapy, such as bronchial and buccal mucosa and even breast epithelium, an additional time factor may be required [4].…”
Section: Description Of Modelmentioning
confidence: 99%
“…A partial justification for this deterministic approach is that the phenomenon of subpopulation extinction, which is often the main reason for replacing a deterministic by a more detailed stochastic analysis (e.g. Tan, 2002;Sachs et al, 2007), is not as important in the present context as in many other population dynamics models, because on the present picture rapid alterations can rapidly resurrect an extinct subpopulation. We will assume the time-development of the cell population is governed by the following proliferation-alteration system of ordinary differential equations:…”
Section: Assumptionsmentioning
confidence: 99%